Return, Remembrance and Redemption: Hauntology and the Topography of Trauma in The Virtues and This Is England '88. Issue 1 (January 2022) - Anderson, Jack
Abstract : This article takes a hauntological approach to explore Shane Meadows's preoccupation with (post)traumatic return, focusing on the TV series The Virtues (Channel 4, 2019) and This Is England '88 (Channel 4, 2011), which are correlatives in their sophisticated explication of hauntological trauma. Using Jacques Derrida's theoretical neologism 'hauntology', the haunting cycles which are signatures in Meadows's work are understood as spectres of an unresolved past and symptoms of repressed knowledge. As explored by Meadows, the psychological breakdowns of key characters Joseph and Lol are articulated as a ghostly resurfacing of unprocessed trauma from the past. By highlighting Meadows's use of return, remembrance and redemption as a triadic narrative pattern, the article will show how Meadows depicts the transformative efficacy of traumatic return through using the haunting as a potentially restorative device.